Automated clothesline system / Farhana Izzati Abdul Rahman & Nur Amira Hamdan - Abdul Rahman, Farhana Izzati; Hamdan, Nur Amira (2015)
The Malaysian female labour force always working at least nine hours per day. Thus, it can interfere their time to do some chores especially laundry. Since Malaysia is located on top of the equator line, it causes to experience rain state and damp during the year. This matter sometimes cause problem to the female labour force when washed clothes are not dry and have unpleasant smell. In order to lighten their burden, the project proposed an automatic clothesline system. Automated Clothesline System is a system that can detect the rain and bring the clothes to a sheltered place automatically with the capability to pull the clothesline or washing line hand-free. This project uses sensors, microcontroller and motor. The sensor used for the system was water sensor. The microcontroller used was Arduino UNO and DC motor was used for the motor circuit. All circuits were constructed and tested and the microcontroller was programmed so that the tor control system can be implemented. The circuits were integrated and tested before the prototype was fabricated in a miniature model that represented the whole system. This project was found to be viable that it can detect rain and bring the clothes to sheltered place.